THE INFLUENCE OF GOING CONCERN, COMPANY SIZE, KAP SIZE AND PROFITABILITY ON AUDITOR SWITCHING PROPERTY AND REAL ESTATE 2016 - 2019 - Zubir, Zubir (International Journal of Business and Information Technology, 2020)
The purpose of this study is to determine the effect of going concern on auditor switching on property and real estate in 2016-2019, to determine the effect of company size on auditor switching on property and real estate in 2016-2019, to determine the effect of KAP size on auditor switching on property and real estate 2016 - 2019, to determine the effect of profitability on auditor switching on property and real estate in 2016 - 2019, and to determine the effect of going concern, company size, KAP size and profitability on auditor switching on property and real estate. estate 2016 - 2019. The results of the research show that simultaneously going concern, company size, KAP size and profitability do not affect auditor switching, and partially going concern, company size, KAP size and profitability have no effect on auditor switching